Methods and tools for encoding the WordNet.Br sentences, concept glosses, and conceptual-semantic relations - Dias-da-Silva, Bento C. [UNESP]; Di Felippo, Ariani [UNESP]; Hasegawa, Ricardo (Springer Nature, 2006)
This paper presents the overall methodology that has been used to encode both the Brazilian Portuguese WordNet (WordNet.Br) standard language-independent conceptual-semantic relations (hyponymy, co-hyponymy, meronymy, cause, and entailment) and the so-called cross-lingual conceptual-semantic relations between different wordnets. Accordingly, after contextualizing the project and outlining the current lexical database structure and statistics, it describes the WordNet.Br editing GUI that was designed to aid the linguist in carrying out the tasks of building synsets, selecting sample sentences from corpora, writing synset concept glosses, and encoding both language-independent conceptual-semantic relations and cross-lingual conceptual-semantic relations between WordNet.Br and Princeton WordNet © Springer-Verlag Berlin Heidelberg 2006.
Keywords: Computer programming languages; Database systems; Linguistics; Numerical methods; Project management; Semantics; Word processing; Building synsets; Concept glosses; Conceptual-semantic relations; Cross-lingual conceptual-semantic relations; Internet